Secondary Metabolites Profiling and Antimicrobial Activities of Ethanol Extract from Jamblang (Syzygium cumini L.) Stem Bark - Fayza Meutia; Yulia Sari Ismail; Lenni Fitri (Postgraduate, University of Mataram, 2025)
This study was conducted to determine the secondary metabolite compounds and evaluate the antimicrobial activity of ethanol extract of jamblang stem bark (Syzygium cumini). The method used in this research is experimental method. The extraction was carried out using the maceration method with 96% ethanol as the solvent. Secondary metabolite compounds of the extract samples were analyzed using a Gas Chromatography-Mass Spectrometry (GC-MS). Antimicrobial activity of the extract against Cutibacterium acnes, Staphylococcus aureus, and Candida albicans using disc diffusion method tested on MHA (Mueller Hinton Agar) media with extract concentrations of 40%, 60%, 80%, and 100%. Each experiment was repeated three times to ensure validity. The results revealed that the extract have dominant compounds such as 7-Tetradecenal (Z), Octadecanoic acid, and n-Hexadecanoic acid. The antimicrobial test showed that the highest inhibition zones were 7.45 mm for C. acnes, 8.04 mm for S. aureus, and 4.60 mm for C. albicans at 100% extract concentration. The inhibition zones increased with higher extract concentrations, indicating a dose-dependent relationship. Compared to the positive control results (20.70 mm; 22.29 mm; and 18.62 mm) the extract showed moderate antimicrobial activity. These findings suggest that jamblang stem bark extract has potential as a natural antimicrobial agent.